Determinant of Effective Participatory Forest Management in Tanzania - Lokina, Razack (Tanzania Journal for Population studies and Development, 2012)
Participatory forest management (PFM) was introduced in Tanzania in 1998. PFM has been adopted as an official strategy to allow for wide participation of stakeholders in forest resource management, with a view that forests can be better managed under close involvement of forest users in decisions regarding appropriate management plans, rules and obligations pertaining to the resource. PFM has three main policy objectives: improved forest quality, improved livelihoods through increased forest revenue, and secure supply of subsistence forest products; and improved forest governance at district and village levels through effective and accountable resource management institutions. Thus PFM has been proposed as a way of both protecting Tanzania's forests and reducing rural poverty. The study utilizes data collected from face-to face interviews with 1000 villagers distributed among 50 villages in two regions of Tanzania. The level of success was assessed in terms of perceived conservation of the reserve forests, and the perceived influence of PFM on the welfare of individuals’ households.The data collected incorporates explicitly spatial elements of NTFP extraction and the enforcement of PFM regulations. Given the nature of the responses, we analyse the data using an ordered Logit model. Preliminary findings indicate that men, larger households, and those households that have their own source of fuelwood are more likely to perceive a particular PFM initiative as successful.